A PATH ANALYSIS OF THE RELATIONSHIP BETWEEN ORGANIZATIONAL AND INDIVIDUAL FACTOR WITH CLINICAL NURSE PERFORMANCE PERCEIVED BY NURSES AT THE SPECIFIC HOSPITALS IN JAKARTA - julianus ake (Jurnal Ilmiah Keperawatan dan Kebidanan Holistic Care, 2019)
Introduction: : A good nurse performance is the expectation of all patients. Performance is the result of quality and quantity of work achieved in carrying out the tasks and responsibilities given to it. The aim of this research was to identify a path of the relationship model between organizational and individual factor toward clinical nurse performance perceived by nurses at the specific hospitals. Method: The study was conducted in two hospitals named National Cardiovascular centre Harapan Kita and National Cancer Dharmais in Jakarta. The method of this research was quantitative method with cross sectional study. The population was clinical nurses with a purposive sampling were collected from 336 clinical nurses, consisted of Clinical Nurse 1 (CNI). Clinical Nurse II (CN II), and Clinical Nurse Ill (CN III). The technique and procedure of data analysis comprised of several steps i.e. 1) a descriptive statistic to describe the research variables, 2) Analytical statistic with two approaches to analyze a measurement model used a Confirmatory Factor Analysis (CFA), whereas to analyze structural model used a path analysis. Results: The result of the CFA test showed that the observed variables on each latent variable are quite fit to reflect latent variable. The result of path analysis on each variable were nurse ladder system and motivation showed that is no direct effect on the nurse performance. The detailed influence on the path model could be described as follow: 1) There are a direct influence of organizational support, work satisfaction, and motivation toward clinical nurse performance, 2) There is no direct influence between nurse ladder system and motivation toward nurse performance, however nurse ladder system and motivation influenced the nurse performance, but both have an effect through organization support and work satisfaction. Conclusion: there are a direct influence of organizational support, work satisfaction, and motivation toward clinical nurse performance, there is no direct influence between nurse ladder system and motivation toward nurse performance, however nurse ladder system and motivation influenced the nurse performance, but both have an effect through organization support and work satisfaction.